Perlindungan Hak Cipta atas Penggunaan Layanan Streaming Netflix untuk Kegiatan Komersial (Studi Kasus Bioskop Mini di Bekasi) - Aulia, Nurul (UM Purwokerto Press, 2024)
The use of streaming services such as Netflix has become a global phenomenon that affects various aspects of life, including the way people consume entertainment. In Bekasi, there is a new trend of mini-cinemas utilizing Netflix streaming services for commercial purposes. This raises questions regarding copyright protection and the legality of the practice. This research aims to explore the extent to which the use of Netflix streaming services in mini-cinemas in Bekasi infringes copyright, as well as to understand the regulations governing the use of digital content for commercial activities in Indonesia. The methodology of this research is normative juridical with a statutory approach in the form of descriptive analytical narrative description being one of the important methods. The results show that the use of Netflix streaming services for commercial activities without authorization is a clear violation of the copyright provisions stipulated in the Indonesian Copyright Law. Mini-cinema owners in Bekasi are largely unaware or ignorant of these regulations, which can lead to serious legal consequences. In addition, this study found that the lack of awareness and understanding of copyright among business actors is one of the main factors causing rampant infringement. Based on these findings, this study suggests the need for further education of the public and businesses on the importance of compliance with copyright law as well as the importance of obtaining appropriate licenses for the use of digital content in commercial activities. This research makes a significant contribution to the field of copyright and legal studies, particularly in the context of the use of streaming services in Indonesia. The findings are expected to serve as a reference for the government and related parties in formulating more effective policies to protect copyright and support the healthy and sustainable development of the entertainment industry.